1997
DOI: 10.1292/jvms.59.995
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Glucocorticoids on Proliferation of Canine Mast Cell Tumor.

Abstract: ABSTRACT. The inhibitory effect of glucocorticoids (GCs) on proliferation of canine mast cell tumor (MCT) was studied using two types of MCT cells; JuMC cells and LuMC cells derived from spontaneous canine cutaneous and intestinal MCT, respectively. In in vitro study, growth of JuMC cells was significantly inhibited with more than 1 nM GCs and apoptotic-like cell death was seen, while that of LuMC cells was never inhibited even with 10 µM GCs. Growth rate of masses in nude mice developed by inoculation of JuMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
2
20
0
1
Order By: Relevance
“…The presence of RARs and RXRs may not always predict the responsiveness of the cell to retinoid treatment. It has recently been shown that the resistance to response is partially attributable to mutations in glucocorticoid receptors [19]. A similar phenomenon might have occurred in the retinoid receptors of the osteosarcoma cells tested in this study.…”
supporting
confidence: 83%
“…The presence of RARs and RXRs may not always predict the responsiveness of the cell to retinoid treatment. It has recently been shown that the resistance to response is partially attributable to mutations in glucocorticoid receptors [19]. A similar phenomenon might have occurred in the retinoid receptors of the osteosarcoma cells tested in this study.…”
supporting
confidence: 83%
“…Frequency and intensity of the chemotherapy may potentially give influences on MDR1 expression, however, none of these factors correlated with MDR1 status of the cell lines investigated in this study [10,23]. Alternatively, TiMC cells may not show induction of MDR1 gene expression in response to some factors, similar to the previously reported MDR1-deficient genotype [13,20].…”
Section: Discussionsupporting
confidence: 54%
“…Cell lines: TiMC, CoMS and LuMC canine MCT cell lines were originated from a cutaneous MCT, an oralmucosal MCT and a gastrointestinal MCT, respectively [10,23]. CoMS cell line was kindly provided by Laboratory of Veterinary Surgery, Department of Veterinary Clinical Sciences, Graduate School of Veterinary Medicine, Hokkaido University.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this study was to assess the response to a previously unpublished chemotherapy protocol for gross MCT in dogs for whom surgery and/or radiotherapy were not suitable using two agents that have shown efficacy against round cell tumours. Prednisolone is widely used in chemotherapy regimens for canine MCTs (McCaw and others 1994, Thamm and others 1999, 2006, Davies and others 2004) and has been shown to inhibit mast cell proliferation in vitro (Takahashi and others 1997); it has also been shown to cause a reduction of size of gross MCTs before radiotherapy (Dobson and others 2004) or surgery (Stanclift and Gilson 2008). Chlorambucil is an alkylating agent that has therapeutic indications in canine round cell tumours, including MCT, lymphoma, chronic lymphoid leukaemia and some myelomas (Carberry and others 1987, Chun and others 2007).…”
Section: Discussionmentioning
confidence: 99%